Egyptian army in politics - "Vatikiotio, P.J." (Bloomington, 1961)
The old order is dying rapidly in Arab countries but has not been completely replaced. The army has emerged as the most progressive element in Arab society today, partially because it is willing to seek "empirically rational solutions" and to push Arab society into the modern age. The revolutionary method of change appears to have been chosen by the army elite in the light of the failure of representative government. The new power elite of army officers seems to provide, for the first time, a basis for political integration and consensus. Political life in Egypt will never be as it was prior to taking over power by the army, but that the claim of the army officers to be leading a revolution which will completely change Arab political community and society has yet to be proven.
Keywords: Political Science